Reimaging reflexivity through a critical theoretical framework: Autoethnographic narratives on becoming a (de)colonised researcher - Sims, Danica Anne (Critical Studies in Teaching and Learning, 2023)
The theory and practice of reflexivity need to be reimagined. In the increasingly globalised world of medical education research, critical perspectives and methodologies for honest, powerful, and just reflexivity are needed. Autoethnography offers a compelling methodological approach to reflexivity, for it interrogates self and interpersonal interactions within socio-cultural contexts through retrospective autobiographical storytelling. Southern theory, decoloniality, and intersectionality together framed critical reflections on power inequalities at personal, contextual, and epistemological levels, throughout the qualitative research process. Reflective questions informed by these theories are included to practically guide individuals in their reflexivity. We are collectively responsible for epistemically- and socially-just research, which means the disruption of normative and hegemonic (i.e., White, Western, Eurocentric, and colonial) research and reflexivity practices; and the development of ethical research that does not reproduce inequalities but welcomes and amplifies other ways of knowing, doing and being.